Association of prenatal lipid‐based nutritional supplementation with fetal growth in rural Gambia. Issue 2 (2nd October 2016) - Johnson, William; Darboe, Momodou K.; Sosseh, Fatou; Nshe, Patrick; Prentice, Andrew M.; Moore, Sophie E.
Abstract: Prenatal supplementation with protein‐energy (PE) and/or multiple‐micronutrients (MMNs) may improve fetal growth, but trials of lipid‐based nutritional supplements (LNSs) have reported inconsistent results. We conducted a post‐hoc analysis of non‐primary outcomes in a trial in Gambia, with the aim to test the associations of LNS with fetal growth and explore how efficacy varies depending on nutritional status. The sample comprised 620 pregnant women in an individually randomized, partially blinded trial with four arms: (a) iron and folic acid (FeFol) tablet (usual care, referent group), (b) MMN tablet, (c) PE LNS, and (d) PE + MMN LNS. Analysis of variance examined unadjusted differences in fetal biometry z ‐scores at 20 and 30 weeks and neonatal anthropometry z ‐scores, while regression tested for modification of intervention‐outcome associations by season and maternal height, body mass index, and weight gain. Despite evidence of between‐arm differences in some fetal biometry, z ‐scores at birth were not greater in the intervention arms than the FeFol arm (e.g., birth weight z ‐scores: FeFol −0.71, MMN −0.63, PE −0.64, PE + MMN −0.62; group‐wise p  = .796). In regression analyses, intervention associations with birth weight and head circumference were modified by maternal weight gain between booking and 30 weeks gestation (e.g., PE + MMN associations with birth weight were +0.462 z ‐scores (95% CI [0.097, 0.826]) in the highest quartile of weight gain but –0.099 z ‐scores (−0.459, 0.260) in the lowest). In conclusion, we found no strong evidence that a prenatal LNS intervention was associated with better fetal growth in the whole sample.